Penunjukan Camat Sebagai Pejabat Pembuat Akta Tanah Sementara Di Kota Tasikmalaya - Muhammad Iqbal Akbar Nugraha; Edith Ratna M.S. (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractThe PPAT and PPATS formations in the city of Tasikmalaya have been fulfilled but the appointment of the head sub-district as PPATS is still being made, with the appointment of the head sub-district as PPATS the head sub-district has additional duties apart from being regional heads as well as PPATS. This study aims to determine the procedures for the appointment of a head sub-district as a temporary PPAT, as well as the obstacles that arise from the appointment of a head sub-district as a temporary PPAT. This research uses normative legal research methods. The results of the research are that in order to be appointed as Temporary PPAT, the sub-district head is obliged to attend education and training organized by the National Land Agency of the Republic of Indonesia, which can be implemented in collaboration with professional organizations for Land Deed Making Officials. The obstacle is that the sub-district head carries out the main and additional duties as regional head as well as the Temporary PPAT, so that in carrying out his duties the PPAT deed is not optimal.keywords: temporary land deed-making; head sub-districtAbstrakFormasi PPAT dan PPATS di wilayah kota tasikmalaya sudah terpenuhi namun penunjukan camat sebagai PPATS masih dilakukan, dengan ditunjuknya camat sebagai PPATS camat memiliki tugas tambahan selain sebagai kepala wilayah juga sebagai PPATS. Penelitian ini bertujuan untuk mengetahui tata cara penunjukan camat sebagai PPAT Sementara, serta kendala yang timbul dari penunjukan camat sebagai PPAT Sementara. Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian ini menunjukan bahwa untuk dapat ditunjuk menjadi PPAT Sementara, maka camat wajib mengikuti pendidikan dan pelatihan yang diselenggarakan oleh Badan Pertanahan Nasional Republik Indonesia yang penyelenggaraannya dapat bekerja sama dengan organisasi profesi Pejabat Pembuat Akta Tanah. Kendalanya adalah camat mengemban tugas pokok dan tugas tambahan sebagai kepala wilayah serta PPAT Sementara, sehingga dalam menjalankan tugasnya membuat akta PPAT tidak maksimal.kata kunci : pejabat pembuat akta tanah sementara; camat